Socio-Semiotic Study of Commercial Signs in The City of Saïda - Mehdaoui SAMIA & Arabi Abd EN NACER (Akofena)
Abstract: This research focuses on an interdisciplinary field, namely onomastics, and more specifically, commercial onomastics. Its analysis is based on a socio-semiotic method, specific to the interpretation of the meanings of signs, colors and names. Strolling through the narrow streets of Saïda, we are captivated by the importance attached to the facades of boutiques, stores and bazaars, their distinctive names and the colors used for their signs. This observation prompted us to question the decisions made regarding the names chosen and the color palette employed. We have conducted research combining semiotic and sociolinguistic study, with the aim of examining the colors and symbols used in signage. The aim is to satisfy our curiosity and understand what attracts shopkeepers to the presentation of their stores; to better decipher the socio-cultural aspect conveyed by these commercial signs.